2022
DOI: 10.1007/s43939-022-00032-4
|View full text |Cite
|
Sign up to set email alerts
|

An electronic synaptic memory device based on four-cation mixed halide perovskite

Abstract: Organic–Inorganic Halide Perovskites (OIHP) have attracted tremendous research interest due to their exceptional semiconducting properties in combination with their facile, solution-based manufacturing performed at low temperatures. Their device applications cover a wide range of domains, while amongst them, photovoltaics is one of the most promising paths towards industrialization. The complex ionic character of perovskites offers a gigantic playground of new dynamic phenomena such as migration of ionic speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…Ultimately, this study demonstrated that MXene-based electrodes perform well in flexible OSCs and have great potential for fabricating electrically readable nonvolatile memory and artificial synaptic devices for simultaneous energy harvesting, memory, and neuromorphic computing applications towards future multifunctional integrated device applications. [20,30:4,5]pyrrolo [3, 2 g]thieno [20,30:4,5]thieno[3,2-b]-indole-2,10-diyl)bis(methanylylidene)) bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononi trile) (Y6), [6,6]-Phenyl C71 butyric acid methyl ester (PC 71 BM), chloro-form (CF) and chloronaphthalene were purchased from Sigma Aldrich. The Ti 3 AlC 2 powder was supplied by XF NANO, Jiangsu, China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, this study demonstrated that MXene-based electrodes perform well in flexible OSCs and have great potential for fabricating electrically readable nonvolatile memory and artificial synaptic devices for simultaneous energy harvesting, memory, and neuromorphic computing applications towards future multifunctional integrated device applications. [20,30:4,5]pyrrolo [3, 2 g]thieno [20,30:4,5]thieno[3,2-b]-indole-2,10-diyl)bis(methanylylidene)) bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononi trile) (Y6), [6,6]-Phenyl C71 butyric acid methyl ester (PC 71 BM), chloro-form (CF) and chloronaphthalene were purchased from Sigma Aldrich. The Ti 3 AlC 2 powder was supplied by XF NANO, Jiangsu, China.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Similarly, Loizos et al deployed a wide variety of synaptic properties of a four-cation RbCsFAMA perovskite device across an inverted solar cell geometry. [6] In addition, a multifunctional device based on n-perovskite/p-spiro-MeOTAD p-n heterojunction diode that enables the integration of photovoltaic, photodetection, and synaptic functionalities in a single cell has been demonstrated. [7] Notably, the functional integration of a ferroelectric oxide thin film and an organic bulk heterojunction (BHJ) to achieve a transistor effect has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding measurements performed at different scanning rates (50-200 mV s −1 ) are shown in Figure S5c (Supporting Information) indicating a minor shift to higher V set values while the scan rate increases in agreement with previous results in 2T memristors based on the same OIHP active layer. [37,38] with bipolar memristive function at lower V D values (by sweeping V D from +25 V to −25 V) are also shown in Figure S6 (Supporting Information), achieving an HRS/LRS ratio of ≈200 at V set = 7 V. The gate bias effect on I D -V D characteristics measured at high V D is depicted in Figure S7 (Supporting Information) indicating that V G is mainly enhancing the current at the LRS with a weak concurrent enhancement of the HRS/LRS ratio.…”
Section: Figure 2amentioning
confidence: 99%
“…[25,26,28,36] Memristive behavior in OIHP is driven by the migration of I− vacancies that form conductive channels, thus exploiting what is usually a degrading ion migration effect in photovoltaic applications. [34,35,37,38] Light can used as an additional input while these devices typically display photoinduced carrier and ion migration. [39] Optoelectronic memristors, in particular, are intriguing candidates for optical sensing because they provide temporary memory and sensory data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation